Associations of suPAR with lifestyle and cardiometabolic risk factors. (22nd May 2014) - Botha, Shani; Fourie, Carla M. T.; Schutte, Rudolph; Kruger, Annamarie; Schutte, Aletta E.
Abstract Background Soluble urokinase plasminogen activator receptor (suPAR), a novel indicator of low‐grade inflammation, is associated with cardiovascular disease and mortality in the general population, while an unhealthy lifestyle influences inflammatory status. We aimed to explore the relationship of suPAR with lifestyle and cardiometabolic risk factors in a black South African population. Design This cross‐sectional study includes 1068 men and women (56·4 ± 10·1 years) from the North West province who took part in the South African leg of the Prospective Urban and Rural Epidemiology (PURE) study in 2010. Captured data included a detailed lifestyle profile (tobacco use, alcohol consumption, physical activity, psychological and dietary intake status), biochemical analyses (suPAR, C‐reactive protein (CRP), glucose and lipids), as well as cardiovascular and anthropometric measurements. Results In exploratory analyses, we observed positive relationships between suPAR and lifestyle factors, such as tobacco use (P‐trend < 0·001), both alcohol consumption (P‐trend = 0·001) and γ‐glutamyl transferase (GGT) (P‐trend < 0·001) and unemployment (P‐trend = 0·002). suPAR and CRP correlated significantly (r = 0·23; P < 0·001). These relationships were confirmed in multiple regression analyses as suPAR independently associated with tobacco use (β = 0·13; P < 0·001), GGT (β = 0·24; P < 0·001) and unemployment (β = 0·07; P = 0·039). suPAR did not associate with the cardiometabolic factors glucose, lipids, blood pressure or measures of adiposity. Conclusion suPAR was independently associated with unhealthy lifestyle behaviours, but not with cardiometabolic risk factors suggesting that suPAR, as known predictor of cardiovascular disease and mortality, is augmented by modifiable cardiovascular risk factors. These findings emphasise the need for a healthy lifestyle to decrease the burden of cardiovascular disease in Africans.